Capital and its structure - Lachmann, Ludwig M. (Kansas City : S. Andrews and McMeel, 1978)
This book aims to rekindle interest in the fundamental problems of capital rather than to present a closed system of generalizations about them; to outline a new approach and to show that it can be applied, with some promise of success, to a number of such problems ranging from the productivity of capital to the demise of the 'strong boom'; to point out the implications of certain economic facts which have been long neglected; and, above all, to emphasize the transmission of knowledge, the interaction of minds, as the ultimate agent of all economic processes.
Includes bibliographical references and index.
rpm 29/09/2017
Loans
Keywords: Capital